Anti-windup based state feedback controller design for constrained T-S systems - Zha, Miao; He, Hanlin; Ju, Kaizhong (Chinese Control Conference, 2019)
This paper discussed an anti-windup (AW) strategy for Takagi-Sugeno (T-S) systems that are subject to input saturation. Different from some existing methods which have to set a state feedback controller first to keep systems table in the linear region of actuator and then design an AW compensator to guarantee system stable when saturate. This paper designed a method that can simultaneously design the state feedback controller and its anti-windup compensator. Based on Lyapunov theory, the stable condition is built using null space of the known matrix. A sufficient stable condition is given in the form of linear matrix inequalities (LMIs). The effectiveness of the proposed method is tested with an example.